Treatment of retention of fetal membranes in cattle - GRUNERT, E.; SARATSIS (Φ. ΣΑΡΑΤΣΗΣ) Ph. (Journal of the Hellenic Veterinary Medical Society, 2018)
The method of treating retention of fetal membranes in cattle depends mainly on etiology. Detachment of the fetal membranes by infusing calcium preparations or administering drugs promoting uterine contractions is effective only in cases due to uterine inertia. Alternatively, it is possible to control retention administrations of broad spectrum antibiotics in adequate dosages, so as to ensure the establishment of a new pregnancy with minimum loss of time. In the rare event of retention due to premature closure of omphalic vessels or to overipe placentomes, it is necessary to take the required therapeutic and precautionary measures.